2012
DOI: 10.3171/2012.3.jns111945
|View full text |Cite|
|
Sign up to set email alerts
|

Significance of Simpson grading system in modern meningioma surgery: integration of the grade with MIB-1 labeling index as a key to predict the recurrence of WHO Grade I meningiomas

Abstract: The clinical significance of the different management strategies related to Simpson Grade I-III resection may have been diluted in the modern surgical era. The MIB-1 index can differentiate tumors with a high risk of recurrence, which could be beneficial for planning tailored optimal follow-up strategies. The results of this study appear to provide a significant backing for the recent shift in meningioma surgery from attempting aggressive resection to valuing the quality of the patient's life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
144
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(155 citation statements)
references
References 40 publications
6
144
2
3
Order By: Relevance
“…Here we revealed that genotype was associated with recurrence independently from the degree of surgical resection completeness (Simpson grade) and histological malignancy (Ki-67 LI and WHO grade), which is known as prognostic factors in meningioma. [32][33][34] TRAKLS type was the most favorable genotype, so in addition to evaluating NF2 status, identifying this genotype from non-NF2 meningioma may help the accurate assessment of the recurrent risk. More recently, TERT promoter and PIK3CA mutations were reported to be associated with highly aggressive behavior or tumorigenesis in meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…Here we revealed that genotype was associated with recurrence independently from the degree of surgical resection completeness (Simpson grade) and histological malignancy (Ki-67 LI and WHO grade), which is known as prognostic factors in meningioma. [32][33][34] TRAKLS type was the most favorable genotype, so in addition to evaluating NF2 status, identifying this genotype from non-NF2 meningioma may help the accurate assessment of the recurrent risk. More recently, TERT promoter and PIK3CA mutations were reported to be associated with highly aggressive behavior or tumorigenesis in meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this is even a controversy for benign meningiomas (WHO Grade I). For benign meningiomas, some authors reported that Simpson Grade I-III resection yielded equivalent results, 31,58,74 while others have advocated for Simpson Grade I or even more radical resection. 28,42,79 This issue becomes even more ambiguous for AMs.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Like others, we believe that there is a subgroup of Grade I meningiomas that demonstrate more aggressive clinical behavior. The MIB-1 labeling index has become a popular tool for predicting recurrence of Grade I meningiomas, 13 although the optimal cutoff has not yet been established. It is possible that markers such as the MIB-1 labeling index may help explain why multifocal meningiomas are more likely to recur both locally and distantly.…”
Section: Multifocal Diseasementioning
confidence: 99%